PERAN CAMAT DALAM PENYELENGGARAAN PEMERINTAHAN DAN DAMPAKNYA TERHADAP KINERJA PEGAWAI PADA KANTOR CAMAT GU KABUPATEN BUTON - Jafar Jafar; Karsadi Karsadi; Sri Sediyaningsih (Journal Publicuho, 2022)
The purpose of this study was to determine how much influence the Camat's leadership had on employee performance at the Gu Subdistrict office of Buton Regency. The research design used is descriptive qualitative. The triangulation technique used is an examination technique that utilizes the use of sources (observations, interviews, literature studies, and archives). Based on the results of the research, in monitoring activities, it appears that efforts to improve employee performance by the Gu District government through visits to work units, seen from employee participation in the form of involvement in assessing the results of implementing program activities that have been scheduled, involvement in assessing the suitability of plans with implementation program activities, involvement in assessing outputs and monitoring activities, are still low. Therefore, employee work discipline must be maintained and the Camat as a leader should continue to increase his motivation by not only being oriented to groups, so as to improve relations both with subordinates and among subordinates.